2019
DOI: 10.1186/s12904-019-0395-8
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver exposure to critical events and distress in home-based palliative care in Germany a cross-sectional study using the Stressful Caregiving Adult Reactions to Experiences of Dying (SCARED) scale

Abstract: BackgroundLay family caregivers of patients receiving palliative care often confront stressful situations in the care of their loved ones. This is particularly true for families in the home-based palliative care settings, where the family caregivers are responsible for a substantial amount of the patient’s care. Yet, to our knowledge, no study to date has examined the family caregivers’ exposure to critical events and distress with home-based palliative care has been reported from Germany. Therefore, we attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Sixteen articles (4)(5)(6)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) address issues related to harms to the physical health of caregivers, highlighting the illness, the impairment, the regions of the body most affected and the main symptoms resulting from the sum of the feeling experienced by caregivers of older adults.…”
Section: Caregivers' Physical Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen articles (4)(5)(6)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) address issues related to harms to the physical health of caregivers, highlighting the illness, the impairment, the regions of the body most affected and the main symptoms resulting from the sum of the feeling experienced by caregivers of older adults.…”
Section: Caregivers' Physical Illnessmentioning
confidence: 99%
“…Among the musculoskeletal disorders most evident in caregivers of older adults due to care, the presence of pain is highlighted (4,6,(10)(11)18,21) in body segments (4,7,(11)(12)(13)(14)16,18) , mainly in the spine, upper and lower limbs, with moderate to intense pain intensity (6,14,17) , characterized by being persistent and uncomfortable. Other authors point to the presence of chronic musculoskeletal diseases in caregivers (4)(5)15) , such as arthritis, osteoarthritis, and osteoporosis.…”
Section: Caregivers' Physical Illnessmentioning
confidence: 99%
“…The family revealed that post-restrain schizophrenia had a desire to take a bath and did not want to take a bath. The relationship between the general tendency to avoid actions in problem situations and the tendency to seek social transfer to overcome stress [12,15,18]. Assertive behavior was also found to correlate with the tendency to be involved in substitution activities.…”
Section: ) Parent Beaten or Deprivedmentioning
confidence: 96%
“…This activity can be realized through the provision of counseling services and health care workers always control families and clients. Multiply family empowerment in managing the various burdens faced by families who care for post-mental disorders [18][19][20]. The need for self-care elimination in schizophrenia post-restrain helps fulfill the need for self-elimination care in schizophrenia post-restrain.…”
Section: ) Parent Beaten or Deprivedmentioning
confidence: 99%
“…Homecare in the palliative setting may challenge the caregiver by the administration of pain relief or other medications as well as a more intimate observation of deterioration and suffering. The Stressful Caregiving Adult Reactions to Experiences of Dying scale has been used to aid in early identification of caregivers stress level due to dying patients’ critical health events 3…”
mentioning
confidence: 99%